Effect of the thickness and surface interface of In2O3 films on the transport and recombination of charges in a polymer solar cell - Omarbekova, G.I.; Аimukhanov, A.K.; Ilyassov, B.R.; Аlexeev, A.M.; Zeinidenov, A.K.; Zhakanova, A.M. (Bulletin of the Karaganda University. “Physics”, 2023)
Indium oxide films were obtained by spin coating from a solution of indium nitrate in ethylene glycol followed by annealing at 300 °C. The influence of the thickness and surface interface of In2O3 films on the optical and photo-electrophysical properties of a polymer solar cell has been studied. It is shown that the surface roughness of the film gradually decreases with a decrease in the thickness of the film to 60 nm, and a further decrease in the thickness of the films leads to its increase. The absorption spectra of the films were measured. The values of the optical band gap width are determined. It was found that with a decrease in the thickness of the films, the width of the forbidden zone (Eg) also decreases. It was found that the parameters of the current-voltage characteristics (VAC) and electrophysical measurements also depend on the thickness and interface of the surface of the In2O3 films. It was found that with an In2O3 film thickness equal to 60 nm, a maximum efficiency value of 3.42 % is observed, at the same time, electrons in the photoactive layer have a maximum charge carrier lifetime and a low recombination rate.
Полимерлі күн элементіндегі зарядтардың тасымалдануы мен рекомбинациясына In2O3 қабыршақтарының қалыңдығы және беттік интерфейсінің әсері
Влияние толщины и поверхностного интерфейса пленок In2O3 на транспорт и рекомбинацию зарядов в полимерном солнечном элементе
Keywords: In2O3 films; polymer solar cell; current-voltage characteristics; impedance spectra